2021
DOI: 10.12997/jla.2021.10.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone Attenuates Pi-induced Vascular Calcification via AMPK-mediated TIMP4 Expression

Abstract: Objective Vascular calcification requires the differentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells. This phenomenon can be enhanced by inflammation and oxidative stress. Zingerone is one of the active ingredients present in the ginger plant that has anti-inflammatory and antioxidant effects. Other functions include anti-obesity, anti-nausea effects. However, the functions of zingerone on vascular calcification has not yet been elucidated. This study investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interestingly and very recently, Zingerone was shown to reverse asthma complications in mice and to prevent Pi‐induced vascular calcification, in vitro, via the activation of AMPK (Lim et al, 2021) these data were very encouraging to us who highlight potential stimulatory effects of Zingerone on the expression of hepatic AMPK.…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly and very recently, Zingerone was shown to reverse asthma complications in mice and to prevent Pi‐induced vascular calcification, in vitro, via the activation of AMPK (Lim et al, 2021) these data were very encouraging to us who highlight potential stimulatory effects of Zingerone on the expression of hepatic AMPK.…”
Section: Introductionmentioning
confidence: 82%
“…In general, mineralization means that calcium is deposited and hardened in hard tissues such as teeth and bones, and calcification refers to abnormal calcium deposition in soft tissues, resulting in a pathological phenotype [37]. In addition to this study, we have reported the results of studies in which other natural products increased bone mineralization but inhibited vascular smooth muscle cell calcification [38,39]. Thus, our findings suggest that policosanol acts by increasing mineralization in hard tissue bone and inhibiting calcification in soft tissue.…”
Section: Discussionmentioning
confidence: 78%
“…For example, AMPK/tissue inhibitors of metalloproteinases 4 signaling cascade in VSMCs were involved in the progress of VC. 186 Interestingly, the knockdown of AMPK by siRNA significantly reversed the anti‐calcification effects of metformin, resveratrol, and exendin‐4 and the reduction of RANKL in the calcified VSMCs. 187 Inhibition of AMPK‐mediated cell deaths was observed in the regulation of aldosterone on high phosphate‐induced VC.…”
Section: Molecular Signaling Pathways On Vcmentioning
confidence: 96%
“…The AMP‐activated protein kinase (AMPK)‐mediated signaling pathway plays a very important role in VC. For example, AMPK/tissue inhibitors of metalloproteinases 4 signaling cascade in VSMCs were involved in the progress of VC 186 . Interestingly, the knockdown of AMPK by siRNA significantly reversed the anti‐calcification effects of metformin, resveratrol, and exendin‐4 and the reduction of RANKL in the calcified VSMCs 187 .…”
Section: Molecular Signaling Pathways On Vcmentioning
confidence: 99%